Eficacia de los informes de pertinencia de la Contraloría General del Estado en los procesos de contratación pública. - Espinoza Correa, Patricia Fernanda (2024)
The present research work examines the effectiveness of the relevance reports issued by the Office of Comptroller General of the State (CGE) in public procurement processes in Ecuador. These reports are mandatory documents requested by public entities to evaluate the relevance and favorability of a contract, ensuring adherence to principles of legality, speed and transparency. The study highlights the historical evolution of the regulations related to these reports, from the Organic Law of Finance of 1830 to the recent reforms in the Comprehensive Organic Criminal Code on Anti-Corruption Matters of 2021. Despite the regulatory and control efforts implemented, the study identifies a significant lack of comprehensive analysis on the real effectiveness of these reports in preventing irregularities and acts of corruption in public management. The main objective is to determine the impact of relevance reports on the reduction of irregularities in public procurement, considering the conditions that affect their effectiveness in preventing corruption. Finally, it is concluded that, although relevance reports are valuable tools, their effectiveness depends on proper implementation and rigorous control by public entities highlighting the need to improve current practices to strengthen transparency and integrity in public procurement processes in Ecuador.